PPLICATION OF RESTITUTION RIGHTS FOR CHILD VICTIMS OF BULLYING AS THE RESPONSIBILITY OF PERPETRATORS IN CIVIL ASPECTS - Kurniasari, Tri Widya; Rahman, Arif; Sari, Elidar (LPPM Universitas Malikussaleh, 2024)
This study aims to determine the application of restitution rights for child victims of bullying as the responsibility of perpetrators in civil aspects. Currently, there are many cases of bullying that affect children as victims. This not only results in physical injury but also psychological harm, with some cases even leading to permanent disability or death. Law Number 35 of 2014, which amends Law Number 23 of 2002 concerning Child Protection, serves as a legal instrument to ensure the protection of all rights inherent in a child. In the process of law enforcement, perpetrators are sometimes subject to criminal sanctions. However, problems arise when the perpetrator refuses to pay restitution as a civil right of the bullying victim. Supreme Court Regulation (Perma) Number 1 of 2022, which pertains to Procedures for Settling Applications and Granting Restitution and Compensation to Victims of Criminal Acts, does not provide a mechanism for coercing perpetrators to pay restitution. This study employs a qualitative research approach, which produces descriptive data on the issues related to the application of restitution rights for child victims of bullying as the responsibility of perpetrators in civil aspects under Law No. 35/2014. The normative legal research approach was conducted to explore the forced right to restitution for bullying victims against bullies, as stipulated by Law No. 35/2014. In practice, in addition to criminal responsibility, bullies can also be held accountable for their actions in civil aspects by granting restitution rights to their victims. The regulation of restitution rights in Law No. 35/2014 and Perma No. 1/2022 serves as evidence that the state acts as an agent in fulfilling legal protection for victims of bullying, both preventively and repressively. However, there is still a need for a legal instrument in the law enforcement process, which could serve as a basis for imposing substitute penalties on perpetrators who refuse to pay restitution to their victims. This would not only have a deterrent effect on bullies but also ensure justice for their victims